Vibration analysis of rub in rotating machinery - Lim, Meng Hee (2013)
Rubbing is one of the most common faults that occu rs in rotating machinery. This paper studies the vibration responses of a rotor system u nder the influence of blade induced rubbing. An experimental study was undertaken to simulate vario us conditions of rubbing in rotor system caused by rotating blades and its corresponding vibration responses are measured and analyzed. Experimental results showed that the effect and vib ration responses caused by blade rubbing is enormous and therefore can be easily detected based on vibration spectrum analysis. Besides this, the severity of rubbing caused by different conditi ons of blades could also be estimated based on the magnitudes and patterns of vibration spectrum.